Community-led plantation model Shahada Cluster, India - VS, Viswadev; Meshram, Manish (2024)
The NATURE+ initiative for community-led plantations aims to restore degraded lands and improve livelihoods. Led by the Alliance of Bioversity International and CIAT as part of CGIAR's research portfolio, this initiative is driving innovation and science to transition food, land, and water systems onto more resilient and sustainable pathways. The BAIF Development Research Foundation being the implementing partner for the initiative is partnering with multiple CGIAR institutes and research partners to develop Nature+ models for transforming the agrifood system. Under the Workpackage 3 Restore of this initiative BAIF has been working with communities for developing community led approach for land restoration. By combining the traditional knowledge of local communities with agroforestry, the NATURE+ initiative is promoting sustainable land use and biodiversity conservation. The Shahada cluster in Nandurbar District of Maharashtra, India is a successful example of this approach, showcasing the potential for community-led initiatives to drive positive change and promote a nature-positive future. Through the establishment of Non-Timber Forest Products nurseries (NTFPs), afforestation on community lands, and the conservation of endemic plant species, this initiative is not only restoring ecological balance but also improving community well-being and promoting sustainable livelihoods. Through a collaborative effort between the community and government agencies, a community-led plantation initiative was successfully implemented, resulting in the planting of 18,200 plants, 6,000 seeds, and 9 species across 19 hectares of land within a 2-year timeframe. This achievement was made possible through the convergence of project initiatives, government schemes and community-led efforts, with the support of local villagers in three villages.